The Association Between Mental Health, Social-Emotional Health, And Child Development in Preschool Children: A Structural Equation Modelling Approach - Chatarina Suryaningsih; Fides Adiviso; Esteve Adrian Estiva; Emerson Aliswag; Michael Aggari; Mark Santos (Gema Lingkungan Kesehatan, 2025)
Preschool-aged children are particularly vulnerable to mental health disorders, which can significantly impact their social and developmental outcomes. This study aims to model the associations between mental health, social-emotional health, and child development in preschool children, emphasizing its relevance to child health policy and intervention strategies. Utilizing a quantitative, correlational, cross-sectional design with Structural Equation Modeling (SEM) analysis, the research involved 156 preschool children aged 72 months. SEM was chosen for its ability to assess complex relationships among multiple variables while controlling for measurement errors, making it more suitable than traditional regression methods. The findings indicate that the average levels of mental health and social-emotional health, as well as growth and development, were within normal limits. However, certain indicators revealed delays that warrant monitoring. A significant correlation was found between child development and both mental and social-emotional health, highlighting a predictive relationship that suggests mental health significantly influences child development. This supports the acceptance of the first hypothesis (H1) while rejecting the null hypothesis (H0). The implications of these results are critical for health workers and educators, suggesting the need for early detection programs for mental health issues in preschool settings. By integrating tools like the Strengths and Difficulties Questionnaire (SDQ) into routine assessments, this study provides actionable recommendations for improving child mental health interventions within educational policies.